Heterogeneous glycosylation and methylation of the Aeromonas caviae flagellin. Issue 4 (18th July 2022) - Lowry, Rebecca C.; Allihaybi, Laila; Parker, Jennifer L.; Couto, Narciso A. S.; Stafford, Graham P.; Shaw, Jonathan G.
Abstract: Bacterial swimming is mediated by the rotation of a flagellar filament. Many bacteria are now known to be able to O ‐glycosylate their flagellins, the proteins that make up the flagellar filament. For bacteria that use nonulosonic acid sugars such as pseudaminic acid, this glycosylation process is essential for the formation of a functional flagellum. However, the specific role of glycosylation remains elusive. Aeromonas caviae is a model for this process as it has a genetically simple glycosylation system. Here, we investigated the localization of the glycans on the A. caviae flagellum filament. Using mass spectrometry it was revealed that pseudaminic acid O‐glycosylation was heterogeneous with no serine or threonine sites that were constantly glycosylated. Site‐directed mutagenesis of particular glycosylation sites in most cases resulted in strains that had reduced motility and produced less detectable flagellin on Western blots. For flagellin O ‐linked glycosylation, there is no known consensus sequence, although hydrophobic amino acids have been suggested to play a role. We, therefore, performed site‐directed mutagenesis of isoleucine or leucine residues flanking the sites of glycosylation and demonstrated a reduction in motility and the amount of flagellin present in the cells,  indicating a role for these hydrophobic amino acids in the flagellin glycosylation process. Abstract : Flagellin glycosylation is required for swimming motility in Aeromonas . Here, we show that O‐glycosylation was heterogeneous with no serine or threonine sites that were constantly glycosylated, and mutation of several sites was found to affect motility. Data herein suggest that hydrophobic amino acids play a role in the glycosylation process.